(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the use of the verb "yukunmoq" (to bow or kneel) in Zahiriddin Muhammad Babur’s "Babur-name" and its connection to various forms of etiquette. The study analyzes how Babur uses this verb to convey respect, political, and diplomatic relations, as well as family and kinship ties. The act of kneeling, symbolized by "yukunmoq," plays a significant role in expressing respect within the Timurid royal court and in various social and political contexts. Babur’s portrayal of this verb reflects its role not only in showing deference to elder relatives and rulers but also as part of statecraft and diplomatic protocols. The article highlights how Babur uses "yukunmoq" to reinforce familial bonds, loyalty, and political power dynamics. Furthermore, the study explores how these practices in Babur’s time align with the broader concepts of etiquette, focusing on the relationship between power, respect, and hierarchical structures in the Timurid empire. The analysis of "yukunmoq" sheds light on its importance in both personal and state relations, offering insights into the cultural and diplomatic norms of the era.